Partial splenic artery embolization: an alternative management strategy for resistant thrombocytopenia of immune thrombocytopenic purpura (ITP) - L. K. Dissanayake (Sri Lanka Journal of Medicine, 2018)
A 69-year-old male presented with haematuria due to a recurrent carcinoma of the bladder in the background of resistant thrombocytopaenia with immune thrombocytopenic purpura. He required frequent platelet transfusions and was a high risk surgical candidate. Partial splenic artery embolization was performed with selective catheterization of the splenic artery. The initial platelet count of 32 x 109/L showed a marked increase after 48 hours, to 251 x 109/L. No complications such as post embolization syndrome were observed. This case report highlights that splenic artery embolization is a stand-alone alternative therapy, for selected patients with ITP having resistant thrombocytopaenia, especially in nonsurgical candidates.